Vitamin D status among apparently healthy individuals in the UAE: a systematic review - Alshamsi, Maitha Abdulla; Fatima, Wafeeqa; Al Teneiji, Maitha Tareq; Srinivasamurthy, Suresh Kumar (Frontiers in Nutrition, 2025)
Background/objectivesVitamin D deficiency is a global health concern, particularly in regions with abundant sunlight, such as the UAE. This study aims to systematically review and meta-analyze available data on vitamin D levels in apparently healthy individuals in the UAE, categorizing findings by demographic factors, including age, gender, and ethnicity. The goal is to assess the extent of deficiency and identify potential contributing factors.MethodsA systematic review was conducted following PRISMA guidelines. PubMed and SCOPUS databases were searched for studies reporting serum vitamin D levels in healthy individuals in the UAE. Eligible studies included cross-sectional, retrospective, prospective, and comparative designs. Data were extracted and analyzed, with vitamin D levels categorized as deficient, insufficient, or normal. Study quality was assessed using a modified Newcastle–Ottawa scale for single-arm studies.ResultsA total of 35 studies involving 28,260 participants were included. Reported vitamin D levels ranged from 5.2 ± 2.8 ng/mL to 42.5 ± 19.5 ng/mL. The pooled mean (SD) for adults above 18 years was 17.63 ng/mL (95% CI: 14.28 to 20.99) indicating widespread deficiency. Among participants, 65% were female, 34% were male, and 1% were infants. Severe deficiency was noted in infants and children, though limited studies focused on these groups.ConclusionDespite high sunlight exposure, vitamin D deficiency is prevalent in the UAE, likely due to cultural clothing practices, limited outdoor activities, darker skin pigmentation, and dietary insufficiencies. Further research on vulnerable populations is needed. Variations in assay methods used across studies (e.g., RIA, ECLIA, LC–MS/MS) may have influenced reported vitamin D levels and contributed to heterogeneity in findings.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024587972, Identifier, CRD42024587972.